2020
DOI: 10.3390/biom10020216
|View full text |Cite
|
Sign up to set email alerts
|

hNGF Peptides Elicit the NGF-TrkA Signalling Pathway in Cholinergic Neurons and Retain Full Neurotrophic Activity in the DRG Assay

Abstract: In the last decade, Nerve Growth Factor (NGF)-based clinical approaches have lacked specific and efficient Tyrosine Kinase A (TrkA) agonists for brain delivery. Nowadays, the characterization of novel small peptidomimetic is taking centre stage in preclinical studies, in order to overcome the main size-related limitation in brain delivery of NGF holoprotein for Central Nervous System (CNS) pathologies. Here we investigated the NGF mimetic properties of the human NGF 1–14 sequence (hNGF1–14) and its derivatives… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 75 publications
0
8
0
Order By: Relevance
“…NGF and its receptors (TrkA and p75NTR) are implicated in cancer growth, CSC proliferation, and immune system evasion [ 21 ]. p75NTR has been shown to exert anti-apoptotic functions, possibly upon stimulation by the precursor form of NGF (proNGF), in tumor growth and spreading, which is largely independent of the mitogenic NGF/TrkA pathway [ 22 ]. Despite preliminary indications regarding the role of p75NTR maturation in cancer progression, the control of p75ICD generation by regulated cleavage and its expression and distribution in LSCC of relevance for cancer progression and metastatization have not been addressed so far.…”
Section: Discussionmentioning
confidence: 99%
“…NGF and its receptors (TrkA and p75NTR) are implicated in cancer growth, CSC proliferation, and immune system evasion [ 21 ]. p75NTR has been shown to exert anti-apoptotic functions, possibly upon stimulation by the precursor form of NGF (proNGF), in tumor growth and spreading, which is largely independent of the mitogenic NGF/TrkA pathway [ 22 ]. Despite preliminary indications regarding the role of p75NTR maturation in cancer progression, the control of p75ICD generation by regulated cleavage and its expression and distribution in LSCC of relevance for cancer progression and metastatization have not been addressed so far.…”
Section: Discussionmentioning
confidence: 99%
“…GW441756 is a highly specific inhibitor of TrkA. Numerous studies have proved that GW441756 has a good effect on TrkA inhibition (35,36), so it was applied in the present study. The present results demonstrated that TrkA receptor inhibition completely blocked these functions of NGF.…”
Section: Discussionmentioning
confidence: 99%
“…The study by Triaca et al investigates the therapeutic potential of small stable nerve growth factor (NGF) peptides as tropomyosin receptor kinase A (TrkA) agonists for treating pathologies of the central and peripheral nervous system [23]. NGF is the founding member of a family of extracellularly secreted growth factors in the nervous system that collectively are called neurotrophins, which also include brain-derived neurotrophic factor, neurotrophin-3, and neurotrophin 4/5 [24].…”
mentioning
confidence: 99%
“…An alternative and possibly promising approach has been to design small peptide ligands based on the N-terminal region in NGF, which binds the extracellular portion of the TrkA receptor. In this issue, Triaca et al investigated the ability of peptide derivatives of human NGF (hNGF) to activate TrkA receptor signaling [23]. The authors found that a small peptide, encoding amino acids 1-14 in the N terminal region NGF (hNGF1-14), was able to trigger established TrkA pathways with high efficacy.…”
mentioning
confidence: 99%
See 1 more Smart Citation